Physiological Adaptations to Hypoxic vs. Normoxic Training during Intermittent Living High - De Smet, Stefan; van Herpt, Paul; D'Hulst, Gommaar; Van Thienen, Ruud; Van Leemputte, Marc; Hespel, Peter (Frontiers in Physiology, 2017)
In the setting of ‘living high’, it is unclear whether high-intensity interval training (HIIT) should be performed ‘low’ or ‘high’ to stimulate muscular and performance adaptations. Therefore, ten physically active males participated in a 5-week ‘live high – train low or high’ program (TR), whilst eight subjects were not engaged in any altitude or training intervention (CON). Five days per week (~15.5 h per day), TR was exposed to normobaric hypoxia simulating progressively increasing altitude of ~2000 – 3250 m. Three times per week, TR performed HIIT, administered as unilateral knee-extension training, with one leg in normobaric hypoxia (~4300 m; TRHYP) and with the other leg in normoxia (TRNOR). ‘Living high’ elicited a consistent elevation in serum erythropoietin concentrations which adequately predicted the increase in hemoglobin mass (r=0.78, P<0.05; TR: +2.6%, P<0.05; CON: -0.7%, P>0.05). Muscle oxygenation during training was lower in TRHYP versus TRNOR (P<0.05). Muscle homogenate buffering capacity and pH-regulating protein abundance were similar between pretest and posttest. Oscillations in muscle blood volume during repeated sprints, as estimated by oscillations in NIRS-derived tHb, increased from pretest to posttest in TRHYP (~80%, P<0.01) but not in TRNOR (~50%, P=0.08). Muscle capillarity (~15%) as well as repeated-sprint ability (~8%) and 3-min maximal performance (~10-15%) increased similarly in both legs (P<0.05). Maximal isometric strength increased in TRHYP (~8%, P<0.05) but not in TRNOR (~4%, P>0.05). In conclusion, muscular and performance adaptations were largely similar following normoxic versus hypoxic HIIT. However, hypoxic HIIT stimulated adaptations in isometric strength and muscle perfusion during intermittent sprinting.